Temporary agency work and precarious employment: A review of the current situation in Australia and New Zealand - John Burgess; Julia Connell; Erling Rasmussen (Management Revue, 2005)
This paper reviews three key issues associated with temporary agency work (referred to as agency work herewith) by drawing on Australian and New Zealand trends and experiences. First, the authors contend that it is surprising, in light of its high flexibility, that agency work constitutes a relatively small proportion of total employment in both countries. This article presents several reasons which can provide an explanation for employers' relatively limited use of agency employment. These reasons also show that agency work must be seen as part of the wider expansion of atypical employment arrangements. Second, the paradoxical mix of glamour and precariousness often associated with agency work is discussed. While labour flexibility is often associated with insecurity and precariousness, there are also advantageous forms of agency employment for all parties concerned. Consequently, this article provides an overview of recent research findings. It is evident from the research literature on agency work that there is either an emphasis on its precarious nature or on the individual preferences and choices of the temps themselves. In many countries, extensive regulatory arrangements exist that govern both the agency sector and the agency employment contract. This is not the case, however, in Australia and New Zealand and the effects of this unregulated approach are discussed as is the possibility of regulatory interventions that could be introduced at a future date.
Keywords: 650; temp agency employment; flexibility; regulation; Leiharbeit; Australien; Neuseeland